Challenge Accepted! - The Impcat of Goal Achievement on Subsequent User Effort and Implications of a Goal's Difficulty - von Rechenberg, Tobias; Gutt, Dominik (Proceedings of the 24th Conference on Information Systems (ECIS), Istanbul)
We empirically investigate the impact of successful goal achievement on future effort to attain the next goal in a recurring goal framework. We use data from a popular German Question & Answer community where goals are represented in the form of badges. In particular, our analysis of this data hinges on the fact, that in this Question & Answer community, badges in a hierarchical badge system are in-creasingly challenging to attain up to a certain badge. After this certain badge, the difficulty level sud-denly drops and remains constant throughout up to the last badge in the hierarchy. Our findings indi-cate that after successful badge achievement users increase their subsequent effort to attain the next badge, but only as long as badges represent a challenge to the user. According to our analysis, we identify self-learning to be the key driver of this behavior.

Goals as Reference Points: Empirical Evidence from a Virtual Reward System - von Rechenberg, Tobias; Gutt, Dominik; Kundisch, Dennis (Decision Analysis)
Heath et al. (1999) propose a prospect theory model for goal behavior. Their analytical model is based on the assumption that goals inherit the main properties of the prospect theory value function, i.e., reference point dependence, loss aversion, and diminishing sensitivity. We investigate whether these main properties transfer to goal behavior in the field. We take user activity data from a gamified Question & Answer community and analyze how users adjust their contribution behavior in the days surrounding goal achievement, where goals are represented by badges. We find that users gradually increase their performance in the days prior to earning a badge, with performance peaking on the day of the promotion. In subsequent days, user performance gradually diminishes again, with the decline being strongest on the day immediately following the badge achievement. These findings reflect the characteristic S-shape of the prospect theory value function which is convex below the reference point and concave above it. Employing the target-based approach, we can interpret the value function as a cumulative density function of a unimodal probability distribution. Our results suggest that it is more likely that active members of the community focus on the next badge relative to the status already achieved, as their next goal and are less likely to focus on more remote (higher-ranked) badges. Our results thus support the transferability of the main properties of the prospect theory value function to goal behavior in the field and suggest a distinct shape of the value function around goals.

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Structure and Online Rating Distributions - Herrmann, Philipp; Gutt, Dominik; Rahman, Mohammad (INFORMS Annual Meeting)

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Structure and Online Rating Distributions - Herrmann, Philipp; Gutt, Dominik; Rahman, Mohammad (NBER Summer Institute on the Economics of Information Technology and Digitization)

Money Talks (Even) in the Sharing Economy: Empirical Evidence for Price Effects in Online Ratings as Quality Signals - Gutt, Dominik; Kundisch, Dennis (Proceedings of the 37th International Conference on Information Systems (ICIS), Dublin, Ireland)
Recent literature reports concerns about implausibly high Overall ratings in the sharing economy, which undermines the credibility of this rating as a quality signal. This study empirically investigates the relationship between quality and price, commonly captured by the Value dimension in multidimensional rating systems, to reveal whether reviewers form a perception of quality that they then express in the Value dimension, rather than in the Overall rating. We test our hypotheses on a comprehensive panel dataset for 14,859 Airbnb listings in New York. Our preliminary empirical findings show that an increase in price leads to a significant and substantial decrease in the Value rating, suggesting that Value ratings can offer a valuable source of information for potential buyers in addition to the supposedly inflated Overall rating. Moreover, this mechanism has substantial implications for potential buyers who seek to evaluate a listing’s quality and for a seller’s price setting.

How do different Sources of the Variance of Online Consumer Ratings matter? - Zimmermann, Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barrie (Workshop on IS Design and Economic Behavior (ISDEB))

Supporting Business Model Idea Generation Through Machine-generated Ideas: A Design Theory - John, Thomas (Proceedings of the 37th International Conference on Information Systems (ICIS), Dublin, Ireland)
Successful business model innovation is impossible without innovative business model ideas. When generating such ideas, humans make use of two properties of the human cognitive system: First, their ability to build up knowledge (i.e., raw material for new ideas), and second, their ability to flexibly recombine that knowledge. While these properties enable humans to generate innovative ideas, the amounts of knowledge and cognitive flexibility that humans can possess are limited, which in turn limits human idea generation capability. With business model idea generators, a new class of information systems is proposed that can contribute to alleviating the limits that constrain human idea generation. The ideas that such idea generators produce can complement human business model ideas, thereby increase the probability for high-quality ideas, and eventually raise the odds of successful business model innovation. The contribution is a design theory that describes the architecture of the proposed idea generators.

Business Model Modeling Languages as Tools for Innovation: Theory and Empirical Evidence - John, Thomas

Vergleichende Betrachtung von Software-Werkzeugen zur Geschäftsmodellentwicklung - Strotmeyer, Sebastian; John, Thomas; Kundisch, Dennis (Multikonferenz Wirtschaftsinformatik (MKWI))

Supporting Business Model Idea Generation Through Machine-generated Ideas - Towards a Design Theory - John, Thomas (AIS SIGPRAG Pre-ICIS Workshop: Practice-based Design and Innovation of Digital Artifacts)

Sharing Means Caring? Hosts' Price Reactions to Rating Visibility - Gutt, Dominik; Herrmann, Philipp (Proceedings of the 23rd European Conference on Information Systems (ECIS), Münster)
We empirically investigate how hosts on Airbnb, a popular peer-to-peer website for fee-based sharing of under-utilized space, adjust their prices once their offering gets a visible star rating for the first time. We use data for over 14,000 offerings from Airbnb which we collected for New York City. Our findings indicate that hosts whose offerings achieve star rating visibility significantly increase their prices by an average of 2.69 € more than hosts with comparable offerings who do not experience this rating visibility during the time of observation. Out of all offerings who achieve rating visibility, we identify the upper quartile of hosts to be the main driver of this price increase, whereas the first 75% percent show only a marginal price reaction. These results can serve as a first step towards understanding the motivation of people to provide assets to the sharing economy.

Economics and Value of IS - Han, K.; Kundisch, Dennis; Weinhardt, C.; Zimmermann, Steffen

Rating Aggregation in Multi-Dimensional Rating Systems: How Do Reviewers Form Overall Ratings? - Gutt, Dominik; Kundisch, Dennis (INFORMS Annual Meeting)

How do Different Sources of the Variance of Consumer Ratings Matter? - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth)
We examine the effect of the variance of consumer ratings on product pricing and sales using an analytical model, which considers goods that are characterized by experience attributes and informed search attributes (i.e., experience attributes that were transformed in search attributes by consumer ratings). For pure informed search goods, equilibrium price increases and demand decreases in variance. For pure experience goods, equilibrium price and demand decrease in variance. For hybrid goods with low total variance, equilibrium price and demand increase with an increasing relative share of variance caused by informed search attributes when the average rating and total variance of ratings are held constant. Hence, risk-averse consumers may prefer a more expensive good with a higher variance of ratings out of two similar goods with the same average rating. Moreover, our analytical model provides a theoretical foundation for the empirically observed j-shaped distribution of consumer ratings in electronic commerce.

DUC - Fostering Diversity Aspects in Higher Education by eLearning and User generated Content - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Rechuel, R. (Proceedings of E-LEARN 2015 - World Conference on E-Learning)

Behavioral Mechanisms Prompted by Virtual Rewards: The Small-Area Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the 23rd European Conference on Information Systems (ECIS))

Interactions in IS Project Portfolio Selection: Status Quo and Perspective - Müller, M.; Meier, Christian; Kundisch, Dennis; Zimmermann, Steffen (Wirtschaftsinformatik Proceedings)

Creativity Through Cognitive Fit: Theory and Preliminary Evidence in a Business Model Idea Generation Context - John, Thomas; Kundisch, Dennis (Wirtschaftsinformatik Proceedings)

Why Fit Leads to Surprise: An Extension of Cognitive Fit Theory to Creative Problems - John, Thomas; Kundisch, Dennis (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth, USA)
Cognitive fit theory (CFT) provides guidance for how best to represent information that is relevant for solving a given problem. CFT is widely established in information systems research and its validity has been demonstrated in a great variety of contexts. However, of the two major types of problems that exist (i.e., routine and creative problems) prior CFT research has addressed only one: routine problems. Creative problems, despite their importance, have been left unaddressed. Therefore, based on the visual sketching model of problem solving, we propose an extension of CFT and thereby demonstrate that cognitive fit can promote problem solving performance also for creative problems. In doing so, we extend the boundary of CFT and add to creativity research a previously unknown cognitive mechanism for promoting creative performance: cognitive fit. Moreover, we contribute to general problem solving research by bridging the gap between problem solving in creativity and information systems research.

IT Project Portfolio Selection in the Presence of Project Interactions - Meier, Christian

On the Activating Power of Gamification – Empirical Evidence from an Online Community - Mutter, Tobias

Different Sources of the Variance of Online Consumer Ratings and their Impact on Price and Demand - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry

Are Requirements for Graduates of Master and PhD Programs in Business and Information Systems Engineering Changing? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Eymann, T.; Kundisch, Dennis; Recker, J.

Ändern sich die beruflichen Anforderungen an Masterabsolventen und Doktoranden der Wirtschaftsinformatik? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Herausforderungen und Chancen eines Wechsels zwischen Hochschulsystemen - Eymann, T.; Kundisch, Dennis; Recker, J.

Vorwort der Tagungsleitung - Suhl, Leena; Kundisch, Dennis

Beating Irrationality: Does Delegating to IT Alleviate the Sunk Cost Effect? - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Management Science)

Using Income Accounting as the Theoretical Basis for Measuring IT Productivity - Kundisch, Dennis; Mittal, Neeraj; Nault, Barrie (Information Systems Research)

Don't take away my Status! - Evidence from the Restructuring of a Virtual Reward System - Mutter, Tobias; Kundisch, Dennis (Computer Networks)

Business Models - An Information Systems Research Agenda - Veit, Daniel; Clemons, Eric; Benlian, Alexander; Buxmann, Peter; Hess, Thomas; Kundisch, Dennis; Leimeister, Jan-Marco; Loos, Peter; Spann, Martin (Business & Information Systems Engineering)

Geschäftsmodelle - Eine Forschungsagenda für die Wirtschaftsinformatik - Veit, D.; Clemons, E.; Buxmann, A.; Hess, T.; Kundisch, Dennis; Leimeister, J.-M.; Loos, P.; Spann, M. (Wirtschaftsinformatik)

Analyzing Cost and Risk Interaction Effects in IT Project Portfolios - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (BIT - Banking and Information Technology)

Behavioral Mechanisms Prompted by Badges: The Goal-Gradient Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the International Conference on Information Systems (ICIS))

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp; Rahman, Mohammad (Workshop on Information Systems & Economics (WISE))

Modeling Languages for Business Models as Tools for Innovation: Towards a Theoretical Foundation - John, Thomas (Proceedings of the Americas' Conference on Information Systems (AMCIS))

Research on Electric Mobility in Germany: Monitoring a Commercial Battery Electric Vehicle Fleet - Görzen, Thomas; Kundisch, Dennis; Ottensmann, C.; Haubrock, A. (Proceedings of the European Electric Vehicle Congress (EEVC))

Towards a Simulation-based Approach for Evaluating Business Models for the Electric Vehicle Market - Weskamp, Christoph; John, Thomas; Suhl, Leena; Kundisch, Dennis; Teetz, A.; Rose, M. (Proceedings of the European Electric Vehicle Congress (EEVC))

The Case for Modeling Consumer Choice Through an Adapted Total Cost of Ownership Approach - John, Thomas; Weskamp, Christoph; Kundisch, Dennis; Suhl, Leena; Flake, S.; Freund, D.; Jung, H. (Proceedings of the European Electric Vehicle Congress (EEVC))

What is the Relationship Between Market Structure and Digitized Customer Experience? - Herrmann, Philipp; Rahman, Mohammad (INFORMS Annual Meeting)

Evaluation von Lerndesigns mit einem webbasierten Classroom Response System in der universitären Lehre - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Neugebauer, J.; Zoyke, A. (Proceedings of the 12. e-Learning Fachtagung Informatik)

Modeling Languages for Business Models as Tools for Innovation - A Systematic Review and Research Agenda - John, Thomas; Kundisch, Dennis (Tagung der Erich-Gutenberg-Arbeitsgemeinschaft Köln e.V.)

Ein TVO-Modell zur Bewertung elektrifizierter Fahrzeugflotten - Görzen, Thomas; Meier, Christian; Kundisch, Dennis (Proceedings der INFORMATIK 2014)

Competition at Last? An Economic Analysis of Current Mobile Data Roaming Regulations in Europe - Herrmann, Philipp; Kundisch, Dennis; Nicolau, V.; Zimmermann, Steffen (Proceedings of the 22nd European Conference on Information Systems (ECIS))

Webbasierte Classroom Response Systeme in der Hochschullehre - eine eimpirische Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Zoyke, A.; Beutner, Marc; Magenheim, J.; Kundisch, Dennis; Herrmann, Philipp; Reinhardt, W. (43. dghd Jahrestagung)

Simulating Consumer Choice of Innovative Business Models for Electric Mobility - Weskamp, Christoph; John, Thomas; Suhl, Leena; Kundisch, Dennis (Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Analyzing Risk Interaction Effects among IT Projects based on Modern Portfolio Theory - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (Tagungsband der Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Competition at Last? An Economic Analysis of Current Mobile Data Roaming Regulations in Europe - Herrmann, Philipp; Kundisch, Dennis; Nicolau, V.; Zimmermann, Steffen (Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Tagungsband MKWI 2014 - Multikonferenz Wirtschaftsinformatik

On Consumer Purchasing Behavior in Electronic Markets - Herrmann, Philipp

Behavioral Mechanisms Towards Badges: The Small-Area Hypothesis - Mutter, Tobias; Kundisch, Dennis

Exploring the Relationship Between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp; Rahman, Mohammad

Support, Supervision, Feedback and Lecturers Role in the use of the Classroom Response Systems PINGO - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Zoyke, A. (Proceedings of the World Conference on E-Learning)

Good Practice Methoden: Klicker Fragen - Kundisch, Dennis

Direkte Rückmeldung erwünscht - Kundisch, Dennis

Entscheidungsunterstützung für szenarium-basierte Risikobewertungen - Kundisch, Dennis; Mutter, Tobias; Wegmann, N. (KoR - Zeitschrift für internationale und kapitalmarktorientierte Rechnungslegung)

Classroom Response Systems - Kundisch, Dennis; Magenheim, Johannes; Beutner, Marc; Herrmann, Philipp; Reinhardt, W.; Zoyke, A. (Informatik-Spektrum)

Business Model Representations: A Cross-Disciplinary Review of the Pragmatic, Semantic and Syntactic Foundations of Existing Approaches - John, Thomas; Kundisch, Dennis (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

Do Non-Monetary Incentive Systems Matter? Evidence From the Restructuring of a Non-Monetary Incentive System in an Online Community - Mutter, Tobias (Proceedings of the 21st European Conference on Information Systems (ECIS))

Towards an Agile Simulation-based Method for Creating, Evaluating and Selecting Business Models - John, Thomas; Weskamp, Christoph; Kundisch, Dennis; Suhl, Leena (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

Designing a Web-Based Classroom Response System - Kundisch, Dennis; Herrmann, Philipp; Whittaker, Michael; Neumann, Jürgen; Magenheim, J.; Reinhardt, W.; Beutner, Marc; Zoyke, A. (Proceedings of the Design Science Research in Information Systems and Technologies 2013 (DESRIST))

Does it Pay Off to Bid Aggressively? An Empirical Study - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Proceedings of the 46th Hawaii International Conference on System Sciences (HICCS))

Online Banking - Meier, Christian; Kundisch, Dennis (Banklexikon)

Geschäftsmodelle als Thema der Wirtschaftsinformatik - Statements zum Themenfeld "Stand der Forschung" - Kundisch, Dennis; John, Thomas

Trading Venue Decision of Private Online Investors - Kundisch, Dennis (International Journal of Electronic Finance)

IT Sourcing Portfolio Management for IT Services Providers - An Approach for using Modern Portfolio Theory to allocate Software Development Projects to available Sites - Zimmermann, Steffen; Katzmarzik, A.; Kundisch, Dennis (The DATA BASE for Advances in Information Systems)

Enhancing the Quality of Financial Advice with Web 2.0 - An Approach Considering Social Capital in Private Asset Allocation - Kundisch, Dennis; Zorzi, R. (Information Systems and e-Business Management)

Investitionsbewertung mit Realoptionen - Kundisch, Dennis; John, Thomas (WISU - Das Wirtschaftsstudium)

PINGO - Umsetzung von E-Learning in der Hoschule in Adaption und Weiterentwicklung des Peer Instruction Ansatzes - Didaktische und organisatorische Reflexion Studierendenaktivierung in Lehrveranstaltungen - Beutner, Marc; Zoyke, A.; Kundisch, Dennis; Herrmann, Philipp; Whittaker, Michael; Magenheim, Johannes; Reinhardt, W. (Kölner Zeitschrift für Wirtschaft und Pädagogik (KWP))

Einsatz mobiler Endgeräte zur Verbesserung der Lehrqualität in Großveranstaltungen - Magenheim, J.; Reinhardt, W.; Kundisch, Dennis; Herrmann, Philipp; Whittaker, Michael; Beutner, Marc; Zoyke, A. (Tagungsband zum E-Learning Symposium 2012)

Designing a Web-Based Application to Support Peer Instruction for Very Large Groups - Kundisch, Dennis; Sievers, M.; Zoyke, A.; Herrmann, Philipp; Whittaker, Michael; Beutner, Marc; Fels, G.; Reinhardt, W.; Magenheim, J. (Proceedings of the International Conference on Information Systems (ICIS))

Does it Pay Off to Bid Aggressively? An Empirical Study - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Proceedings of the International Conference on Information Systems (ICIS))

Does it Pay Off to Bid Aggressively? An Empirical Study - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (13th Workshop on Information Systems and Economics (WISE))

Does it Pay Off to Bid Aggressively? An Empirical Study - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (INFORMS Annual Meeting)

Research on electric mobility in Germany: A systematic review of publicly funded projects - John, Thomas; Kundisch, Dennis; Kammann, Jan; Sauerland, Torben (Proceedings of the European Electric Vehicle Congress (EEVC))

Die Idee der doppelt bedingten Glattung der Volatilität von Hochfrequenten Finanzdaten in einem raumlichen Modell - Peitz, C.; Feng, J.; Kundisch, Dennis (Statistische Woche)

Developing electronic classroom respose apps for a wide variety of mobile devices - Lessons learned from the PINGO project - Sievers, M.; Reinhardt, W.; Kundisch, Dennis; Herrmann, Philipp (Proceedings of the 11th World Conference on Mobile and Contextual Learning (mLearn))

PINGO: Peer Instruction for Very Large Groups - Reinhardt, W.; Sievers, M.; Magenheim, J.; Kundisch, Dennis; Herrmann, Philipp; Beutner, Marc; Zoyke, A. (Proceedings of the 7th European Conference on Technology Enhanced Learning (EC-TEL))

Towards Automated Event Studies Using High Frequency News And Trading Data - Bohn, Nicolai; Rabhi, Fethi; Kundisch, Dennis; Yao, L.; Mutter, Tobias (Proceedings of the 6th International Workshop on Enterprise Applications, Markets and Services in the Finance Industry (FinanceCom))

In need of change: The scientific practice of representing business models - John, Thomas; Kundisch, Dennis (Proceedings of the 14th International Conference on Enterprise Information Systems)

Approaches for Business Model Representation: An Overview - Kundisch, Dennis; John, Thomas; Honnacker, Jörg; Meier, Christian (Proceedings of the Multikonferenz Wirtschaftsinformatik (MKWI))

Towards a Classification Framework for Business Model Representations - Kundisch, Dennis; John, Thomas; Honnacker, Jörg; Meier, Christian (6th International Workshop on Value Modeling and Business Ontology)

Business Model Representation Incorporating Real Options: An Extension of e3-value - Kundisch, Dennis; John, Thomas (Proceedings of the 45th Hawaii International Conference on System Sciences (HICSS))

IT-Projektportfolios mit Projektabhängigkeiten wertorientiert gestalten - Zimmermann, Steffen; Heinrich, B.; Kundisch, Dennis (Organisation des IT-Projekt- und IT-Projektportfoliomanagements)

Algorithmic Trading - Honnacker, Jörg; Kundisch, Dennis (Banklexikon)

Ausserbörslicher Direkthandel - Herrmann, Philipp; Kundisch, Dennis (Banklexikon)

Online Broker / Online Brokerage - Mutter, Tobias; Kundisch, Dennis (Banklexikon)

Zur Bewertung von Verlustgesellschaften nach den Änderungen des §8c KStG durch das Wachstumsbeschleunigungsgesetz - Diller, M.; Kundisch, Dennis; Späth, T. (CORPORATE FINANCE biz)

The Impact of Delegating Decision Making to IT on the Sunk Cost Effect - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (12th Workshop on Information Systems and Economics (WISE))

Sunk Cost Effect: The Impact of Delegating Decision Making to IT - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (INFORMS 2011 Annual Meeting, Track Digital Channel and It Usage)

Sunk Cost Effect: The Impact of Delegating Decision Making to IT - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (7th Symposium on Statistical Challenges in Electronic Commerce Research)

A new Perspective on Resource Interactions in IT/IS Project Portfolio Selection - Kundisch, Dennis; Meier, Christian (Proceedings of the European Conference on Information Systems (ECIS))

The Impact of Interaction Effects Among Software Development Projects on Global Sourcing Decisions - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (5th Global Sourcing Workshop)

IT/IS Project Portfolio Selection in the Presence of Project Interactions - Review and Synthesis of the Literature - Kundisch, Dennis; Meier, Christian (Wirtschaftsinformatik Proceedings)

Partizipieren statt konsumieren, oder: Lohnt sich Engagement in Q&A-Communities? - Herrmann, Philipp; Kundisch, Dennis (Wirtschaftsinformatik Proceedings)

The Impact of Delegating Decision Making to IT on the Sunk Cost Effect - Herrmann, Philipp; Kundisch, Dennis; Rahman, M. (12th Workshop on Information Systems and Economics (WISE))

Vorwort zum Track Integriertes Ertrags-/Risikomanagement in automatisierten Geschäftsprozessen - Müller, G.; Kundisch, Dennis; Sackmann, S.; Romeike, F.

Price Efficiency in Futures and Spot Trading: The Role of Information Technology - Wagener, Martin; Kundisch, Dennis; Riordan, R.; Rabhi, Fethi; Herrmann, Philipp; Weinhardt, C. (Electronic Commerce Research and Applications)

Customer Portfolio Management in E-Commerce - An Analytical Model for Optimization - Sackmann, S.; Kundisch, Dennis; Ruch, M. (Management Research Review)